Me slišiš? Simone Semenič in vprašanje ne več dramske pisave - Troha, Gašper (Amfiteater (Ljubljana), 2021)
In the article, the author analyses three plays by Simona Semenič that were published in the book can you hear me? (2017). At first sight, the three pieces appear to be written in Semenič's now-familiar writing style with no punctuation marks or upper-case initials and no apparent division between dialogues and stage directions. Content-wise, however, the three plays differ significantly from the bulk of the playwright's opus as they represent autobiographical texts which once again establish the character and more or less distinct dramatic action. The article focuses on two questions: Are these still no-longer-dramatic texts? And, what is the status of representation and performativity in them? By analysing the formal and content properties of the three texts, more precisely, through an analysis of the drama character, the relationship between dialogue and monologue and dramatic action, the author shows that indeed these texts establish recognisable dramatic characters and relatively strong dramatic action. In this, they move away from no-longer-dramatic texts as defined by Gerda Poschmann, even though their legacy is still very much present, e.g., in the fragmented writing style.
Keywords: Birgit Haas; Can you hear me?; dramatic text; dramski tekst; Me slišiš?; ne več dramski tekst; no-longer-dramatic text; Semenič, Simona